1981
DOI: 10.1111/j.1528-1157.1981.tb04331.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Prognosis of Epilepsy: Report of a Multi‐institutional Study in Japan

Abstract: A multi-institutional study on the prognosis of patients with epilepsy was performed in Japan from 1975 to 1977, including 20 institutions. The outcome of epileptic seizures and social adjustment 10, 5, and 3 years after the onset of the illness was studied in three different groups of epileptic patients, respectively. The number of successfully followed-up cases was 1,868 in total, follow-up rate being 42%. The data were analyzed statistically by use of analysis of variance. The rate of remission of seizures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
0
3

Year Published

1986
1986
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 10 publications
9
63
0
3
Order By: Relevance
“…While Annegers et al [2] found remission rates higher in patients with generalized seizures than in sub jects with seizures that were focal at onset in their idiopathic group, in our patient popula tion the seizure type did not influence the out come of clinical control. This finding is in agreement with another report which grouped together all epilepsy syndromes in children [15], Partial seizures had a worse prognosis also in the Elwes study [4], and the co-exis tence of several main types of seizures led to a less favourable outcome in an incidence co hort of children without neurodeficit aged 0-19 years and in other studies [16,17], On the other hand, the lack of effect of partial versus generalized seizures in our study can not be related to the proportion of cases with benign rolandic epilepsy. There is no general agree ment on the prognostic value of age at the onset of epilepsy.…”
Section: Prognosis Of Childhood Epilepsysupporting
confidence: 82%
“…While Annegers et al [2] found remission rates higher in patients with generalized seizures than in sub jects with seizures that were focal at onset in their idiopathic group, in our patient popula tion the seizure type did not influence the out come of clinical control. This finding is in agreement with another report which grouped together all epilepsy syndromes in children [15], Partial seizures had a worse prognosis also in the Elwes study [4], and the co-exis tence of several main types of seizures led to a less favourable outcome in an incidence co hort of children without neurodeficit aged 0-19 years and in other studies [16,17], On the other hand, the lack of effect of partial versus generalized seizures in our study can not be related to the proportion of cases with benign rolandic epilepsy. There is no general agree ment on the prognostic value of age at the onset of epilepsy.…”
Section: Prognosis Of Childhood Epilepsysupporting
confidence: 82%
“…In pediatric epilepsy, the natural progression of disease varies not only between patients, but also between and within epilepsy subtypes and syndromes [54,55]. For instance, benign epilepsy with centrotemporal spikes typically occurs between the age of 3 and 14 years and resolves by the age 17 years despite the incidence of cognitive and behavioral disorders [56].…”
Section: Disease Progression and Maturationmentioning
confidence: 99%
“…Seizure disorders are thought to occur in about 1% of the population [1,2]. Although the symptoms of most patients with epilepsy can be controlled with antiepileptic drugs, a substantial number of these patients develop intractable epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Although the symptoms of most patients with epilepsy can be controlled with antiepileptic drugs, a substantial number of these patients develop intractable epilepsy. Surgical treatments of medically intractable epilepsy have undergone many modifications since they were initially introduced as treatments for epileptic seizures [1][2][3]. In tandem with rapid advances in neuroimaging techniques, such as computerized tomography, magnetic resonance imaging and positron emission tomography, electrophysiological techniques which can precisely localize a resectable zone of epileptogenesis have become widely available [4,5].…”
Section: Introductionmentioning
confidence: 99%